Някои типове обособяване в народно-разговорния език (върху материал от българския език в съпоставка с полския) - Крумова, Лилия (Съпоставително езикознание / Сопоставительное языкознание / Contrastive linguistics, 1979)
Some cases of apposition of substantivized adjectives and nouns of the same root are considered. Apposition concerns concrete lexico-semantic groups in definite syntactic positions: 1.Substantivized adjectives and nouns of the same root with emotional connotation, in the position of appositions referring to the subject or object. 2. Substantivized adjectives for kinship relations and nouns from the kinship vocabulary, in the position of appositions to addresses. Because of the special nature of these appositions serving, above all, as means of expressing the attitude of the speaker or author to a given person, they may be considered as appositions of modal and parenthetical nature. The close interdependence of the semantic, morphologic and syntactic features in appositions is discussed. Some Bulgarian-Polish parallels are given as illustrations.